Brand Image dan Country of Origin untuk Memprediksi Purchase Decision Konsumen : Variabel Perceived Quality Sebagai Variabel Mediasi - I Made Genta Wedangga; Keni Keni (Universitas Tarumanagara, 2020)
The purpose of this research is to examine whether 1) brand image and country of origin can predict purchase decision 2) brand image can predict perceived quality 3) perceived quality can predict purchase decision and 4) perceived quality can mediate the effect of brand image on purchase decision. Sample was selected using convenience sampling method amounted to 200 respondents at Jakarta and Tangerang. Data processing techniques using structural equation modeling what helped by SmartPLS.3.2.8 program. The result of this study shows that 1) brand image and country of origin have significant effect to predict purchase decision 2) brand image have significant effect to predict perceived quality 3) perceived quality have significant effect to predict purchase decision and 4) perceived quality can mediate the effet of brand image on purchase decision.